Eksistensi Bentuk Komunikasi Penyiaran RRI Mataram di Era Digital - Yuliandari, Ni Wayan Esty; Widaswara, Rieka Yulita (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
This research aims to examine the existence of RRI Mataram's form of broadcasting in the digital era. RRI Mataram is the only government-owned radio in the city of Mataram which in order to keep up with developments in information and communication technology of course requires innovation in the form of broadcasting so that it continues to exist and does not lose RRI Mataram's loyal listeners. The focus of the research is on aspects of RRI Mataram's broadcasting form in the digital era. This research was designed in a qualitative descriptive manner, using media convergence theory. The results of the research show that RRI Mataram's form of broadcasting communication in the digital era uses three forms of radio which were initially innovated to become digital radio. The three forms are analog radio, digital radio and online radio. Analog radio was the first form of radio which still exists today. Analog radio uses analog signals which can be affected by various factors, such as electromagnetic interference, damage to components, and weather. Secondly, digital radio is radio which in its use uses digital technology to share information with a wide audience. The information which was originally audio is then converted into digital data and then received by the radio. Digital signals have better sound quality than analog signals. The third is internet radio or online radio, internet radio, namely radio that uses an internet connection in its broadcast communication process. Internet radio has a streaming media to provide continuous audio channels that are not found on conventional radio in general. Internet radio is also often called web radio, or net radio.